Rural entrepreneurship in mountainous regions within the severe crisis in Greece - KARAGOUNI GLYKERIA; TRIGKAS MARIOS; PAPADOPOULOS IOANNIS; MPASDEKIS DIMITRIS (Journal of Advanced Research in Social Sciences and Humanities, 2017)
Aim: This paper aims to investigate the realities of starting a business in the countryside, and more specifically, in mountainous regions. This study examines the unique characteristics of the business ecosystem structure in the mountainous Pyli area, Region of Thessaly, Greece, and its population, two central aspects of rural entrepreneurship according to existing literature.Methodology: One-third of the local businesses were included in the field study, which was deemed sufficient for the research’s aims. Research information was gathered from participants via predetermined questions.Findings: The results corroborate previous research and aid in formulating new policies to revitalize Greece’s rural communities, which have been hit hard by the country’s protracted economic downturn.Implications/Novelty: The paper set out to stimulate more generic policy innovation to foster the bottom-up development of local approaches to bolster rural entrepreneurship in mountainous areas, particularly during times of crisis.